2013
DOI: 10.1111/gcbb.12047
|View full text |Cite
|
Sign up to set email alerts
|

Global simulation of bioenergy crop productivity: analytical framework and case study for switchgrass

Abstract: A global energy crop productivity model that provides geospatially explicit quantitative details on biomass potential and factors affecting sustainability would be useful, but does not exist now. This study describes a modeling platform capable of meeting many challenges associated with global-scale agro-ecosystem modeling. We designed an analytical framework for bioenergy crops consisting of six major components: (i) standardized natural resources datasets, (ii) global field-trial data and crop management pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(52 reference statements)
2
22
0
Order By: Relevance
“…The CENTURY model was among the first to be applied to bioenergy sustainability assessment, and it and its derivative DayCent model have been widely used to evaluate corn grain production, corn stover removal, and the dedicated cultivation of switchgrass and Miscanthus from the level of individual sites to national scales (Sheehan et al ., ; Kim & Dale, ; Chamberlain et al ., ; Davis et al ., ; Lee et al ., ; Duval et al ., ). The Environmental Policy Integrated Climate model has also been applied extensively to bioenergy feedstocks in the context of economic analyses (Jain et al ., ; Egbendewe‐Mondzozo et al ., ) and environmental sustainability assessments (Gelfand et al ., ) at scales from regional (Zhang et al ., ) to global (Kang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The CENTURY model was among the first to be applied to bioenergy sustainability assessment, and it and its derivative DayCent model have been widely used to evaluate corn grain production, corn stover removal, and the dedicated cultivation of switchgrass and Miscanthus from the level of individual sites to national scales (Sheehan et al ., ; Kim & Dale, ; Chamberlain et al ., ; Davis et al ., ; Lee et al ., ; Duval et al ., ). The Environmental Policy Integrated Climate model has also been applied extensively to bioenergy feedstocks in the context of economic analyses (Jain et al ., ; Egbendewe‐Mondzozo et al ., ) and environmental sustainability assessments (Gelfand et al ., ) at scales from regional (Zhang et al ., ) to global (Kang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, many bioenergy assessment studies are based on models parameterized under prime conditions and then extrapolated to highly marginal sites, or lacking an explicit independent validation of performance (e.g. Gelfand et al ., ; Kang et al ., ). In the case of the DayCent model, parameterization typically involves adjusting study site and crop parameters by hand in order to match observed real‐world performance for a small number of field trial cases for which extensive data are available (Del Grosso et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These features have lead researchers to propose that CAM plantations could be more resilient to climate change and offer higher productivity on lowgrade and marginal lands than conventional C3 and C4 biomass crops (Borland et al, 2009(Borland et al, , 2014Davis et al, 2011). We tested these hypotheses by (i) constructing a global-scale geospatial productivity model for the CAM biomass candidates Agave tequilana and Opuntia ficusindica, (ii) simulating productivity under present-day and future climate scenarios using outputs from representative concentration pathway (RCP) scenarios presented in the IPCC's 5th Assessment Report (AR5), (iii) applying macro-scale land-use constraints to estimate productivity potential on 'low-grade' lands, and (iv) comparing present-day simulations to outputs of a recently published model for the C4 biomass candidate, Panicum virgatum L. (switchgrass) (Kang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is still a lack of information on where, at what rates, and on what type of land cover is affected by LUC. Recently, however, a number of harmonized databases and process-based biogeochemical models have been developed that could be used to estimate the potential biomass productivity at a global scale from cropland, natural ecosystems and bioenergy crop plantations (Sitch et al, 2003;Monfreda et al, 2008;Portmann et al, 2010;Beringer et al, 2011;Poulter et al, 2011;Kang et al, 2014;You et al, 2014).…”
Section: Introductionmentioning
confidence: 99%